Solar photovoltaic energy system-based shunt active filter for electrical energy quality improvement. (2016) - Saidi, Salem; Abbassi, Rabeh; Hassen, Wafa Ben; Chebbi, Souad
This article presents a harmonic compensation system using a photovoltaic generator (GPV) to improve the supply power quality. The proposed configuration is constituted by a grid connected three-phase inverter, a PV array and a nonlinear load formed by a bridge rectifier feeding a resistive load in series with an inductor. An indirect current control via the method of active and reactive power is proposed to compensate the harmonic currents and reactive power at the point of common coupling while injecting active power from the solar system to the grid. The perturb and observe (P&O) method has been applied to track the maximum power point. The proposed system simulation under MATLAB/Simulink environment proves the robustness of the proposed control approach that simultaneously guarantees the compensation of harmonic currents, the correction of the power factor and the injection of PV power to the grid.